KONSEKUENSI DARI MEKANISME GANDA IKLIM MOTIVASIONAL DAN PASSION DALAM PEKERJAAN PADA PERILAKU PETUGAS KEPOLISIAN - Gaol, Rafidin Lumban; Anita, Rizqa; Hadiyati, Hadiyati (Komunitas Manajemen Kompetitif, 2025)
This study aims to reveal how and why two types of motivational climates in police institutions influence the behavior of individual officers. Specifically, this study explains the reasons why the mastery and performance climates influence two types of passion, namely harmonious and obsessive, which impact differences in proactive behavior and unethical behavior related to work. Furthermore, this study uses primary data obtained through questionnaires to test the hypotheses. The questionnaire consists of closed-ended questions, where respondents select answers based on their circumstances. Data was collected from 356 police officers across various police institutions in one of Indonesia's provinces. SEM-PLS analysis results indicate that the mastery climate has a positive and significant influence on harmonious passion, which in turn enhances proactive work behavior. Additionally, harmonious passion significantly mediates the relationship between a mastery climate and proactive work behavior. Meanwhile, a performance climate has a positive and significant influence on obsessive passion, which drives unethical behavior for work. Obsessive passion also significantly mediates the relationship between a performance climate and unethical behavior for work. Keywords: motivational climate, passion in work, proactive behavior, unethical behavior